Impact of magnetohydrodynamic on hybrid nanofluid flow with slip and heat source over an exponentially stretchable/shrinkable permeable sheet - Radzi, N. A. M.; Wahid, N. S.; Som, A. N. M.; Arifin, N. M. (Lviv Polytechnic National University, 2024)
This research examines the hybrid nanofluid alumina-copper/water flow over a permeable sheet, considering slip, magnetohydrodynamics, and heat source. To analyze the system, the model is transformed into nonlinear ordinary differential equations (ODEs) via the similarity transformation. Numerical solutions are attained through the implementation of the bvp4c function in MATLAB. The study analyzes velocity and temperature profiles, local skin friction, and Nusselt number for various parameters. Moreover, the impact of magnetohydrodynamics on the system is explored. Increasing the magnetic parameter leads to an enlargement of the boundary layer thickness and an elevation in the skin friction coefficient. Overall, this study sheds light on the complex behavior of hybrid nanofluid flows and provides valuable insights into the effects of slip, magnetohydrodynamics, and heat source on the model while also presenting a validated model showcasing the compelling enhancement of heat transfer through the incorporation of copper into alumina nanofluid.